HRYHORII OVKSENTIIOVYCH ANDRUSHCHENKO: LIFE PATH OF THE SCIENTIST AND THE UKRAINIAN SOIL SCIENCE - Hnativ П.; Shvydka Т.; Ivaniuk В.; Poliukhovych М.; Haskevych О.; Parkhuts Б.; Veha Н.; Kunynets Р. (Bulletin of Lviv National Environmental University. Series Agronomy, 2023)
The article describes the life path of the well-known soil scientist H. O. Andrushchenko, professor of Lviv National Environmental University. Historically, soil science in the west of Ukraine started in 1856 in Dubliany when professors Severyn Plakhetko and Emil Godlevskyi began their activities. At the end of the 19th century, Agricultural School in Dubliany was actively developing and in 1880 it acquired the status of Higher Agricultural School, and later - the Academy. Professors Józef Mikulowski-Pomorski and Maryan Gurski focused their work primarily on soil science and soil chemistry. When Hryhorii Andrushchenko moved to Dubliany in 1945 and began his work at the Department of Soil Science, he initiated research of the soils of the western regions of Ukraine, Kazakhstan, countries of the Western Hemisphere and Indochina. Hryhorii Andrushchenko organized modern laboratories for the educational and research work, namely chemical and physical laboratory with a set of appropriate reagents and devices; optical laboratory with the latest equipment, in particular, spectrograph DFS-3, spectrophotometer, microphotometer, photoelectrocolorimeter, Zeiss flame photometer, pH meters; isotope laboratory; the soil museum, in which monoliths of all soils of the western regions of Ukraine were presented. The results of many years of the celebrant’s research have contributed to specification of the indicators that are important for the diagnosis of soils, namely: the ratio of organic and mineral forms of iron, as well as organic and mineral phosphates in soils; rapid changes in the content and composition of phosphates in the profile. The scientist has made a significant contribution to soil cartography, in particular, large-scale soil surveying and generalization of research results.